Domestication Genomics of the Open-Pollinated Scarlet Runner Bean (Phaseolus coccineus L.) - Guerra-García, Azalea; Suárez-Atilano, Marco; Mastretta-Yanes, Alicia; Delgado-Salinas, Alfonso; Piñero, Daniel (Frontiers in Plant Science, 2017)
The runner bean is a legume species from Mesoamerica closely related to common bean (P. vulgaris). It is a perennial species, but it is usually cultivated in small-scale agriculture as an annual crop for its dry seeds and edible immature pods. Unlike the common bean, P. coccineus has received little attention from a genetic standpoint. In this work we aim to 1) provide information about the domestication history and domestication events of P. coccineus; 2) examine the distribution and level of genetic diversity in wild and cultivated Mexican populations of this species; and, 3) identify candidate loci to natural and artificial selection. For this, we generated genotyping by sequencing data (42,548 SNPs) from 242 individuals of P. coccineus and the domesticated forms of the closely related species P. vulgaris (20) and P. dumosus (35). Eight genetic clusters were detected, of which half corresponds to wild populations and the rest to domesticated plants. The cultivated populations conform a monophyletic clade, suggesting that only one domestication event occurred in Mexico, and that it took place around populations of the Trans-Mexican Volcanic Belt. No difference between wild and domesticated levels of genetic diversity was detected and effective population sizes are relatively high, supporting a weak genetic bottleneck during domestication. Most populations presented an excess of heterozygotes, probably due to inbreeding depression. One population of P. coccineus subsp. striatus had the greatest excess and seems to be genetically isolated despite being geographically close to other wild populations. Contrasting with previous studies, we did not find evidence of recent gene flow between wild and cultivated populations. Based on outlier detection methods, we identified 24 domestication-related SNPs, 13 related to cultivar diversification and eight under natural selection. Few of these SNPs fell within annotated loci, but the annotated domestication-related SNPs are highly expressed in flowers and pods. Our results contribute to the understanding of the domestication history of P. coccineus, and highlight how the genetic signatures of domestication can be substantially different between closely related species.